(untitled) (Research, Society and Development, 2023)
This study aims to evaluate through a bibliographic survey the risk of Pressure Injury (PPL) in patients hospitalized in Intensive Care Units (ICU), identifying their related risks and analyzing the main prevention measures and the importance of nursing. A qualitative study of descriptive character, for its elaboration, a literature review was carried out, seeking to achieve the proposed objective. PPL is characterized by changes in the skin, usually close to regions of bony prominence, where a lot of pressure occurs. The injury usually occurs through determinants such as the intensity and duration of pressure associated with tolerance tissues to withstand a certain pressure. Risk factors are: Mobility and impaired activity, sensory perception, factors that reduce the factor tolerance (extrinsic and intrinsic). Prevention and care are a challenge for the team due to the and the high costs to deal with the consequences of the emergence. Nurses use some instruments such as the Braden scale that helps identify the patient at risk and also the risk factors that are associated with assisting in taking decisions for the planning of preventive measures. It is important to conduct further studies on the subject to help in the prevention and treatment of PPL, encouraging the search for new research, in order to inform about the updates of the subject, benefiting the readers in search of innovation, and health itself.